Can Electric Vehicles Aid the Renewable Transition? Evidence from a Field Experiment Incentivising Midday Charging - Andrea La Nauze; Lana Friesen; Kai Li Lim; Flavio Menezes; Lionel Page; Thara Philip; Jake Whitehead (CESifo GmbH, 2024)
In a field experiment tracking 390 electric vehicles minute-by-minute, we show that incentives reduce charging by 17%—27% during peak times and increase it by 34% during midday when solar generation is highest. Peak charging decreases at home, while midday charging rises out of the home. Participants shift and reduce charging, drive less, and run batteries lower. We find heterogeneity based on rooftop solar ownership, commuting, and having a fast home charger. These findings suggest electric vehicles can support the shift from fossil fuels to renewable energy and highlight the enabling role of charging infrastructure.
Keywords: Q41; Q42; Q48; R41; 330; electric vehicles; field experiment; renewable energy; rooftop solar; dynamic electricity prices